The Fourth Reich : the specter of Nazism from World War II to the present - Rosenfeld, Gavriel D. 1967- (Cambridge University Press, 2019)
Between fantasy and nightmare : inventing the Fourth Reich in the Third Reich -- From werewolves to democrats : the Fourth Reich under Allied occupation -- The Fourth Reich turns right : renazifying Germany in the 1950s -- From Germany to the United States : universalizing the Fourth Reich in the turbulent 1960s -- "Hitler in Argentina!" : fictionalizing the Fourth Reich in the long 1970s -- Re-Germanizing the Fourth Reich : from reunification to the Reich citizen